Chemo-sensory characterization of aroma active compounds of native oak wood in relation to their geographical origins - Ghadiriasli, Rahil; Mahmoud, Mohamed A.A.; Wagenstaller, Maria; van de Kuilen, Jan Willem; Büttner, Andrea (Food Research International, 2021)
Oak wood contains aroma-active compounds that contribute significantly to the chemical structure, olfactory and gustatory qualities of alcoholic beverages and vinegars as by-products that have been either fermented and/or aged in oak barrels. The chemical composition of cooperage oak is highly variable, depending on the degree of toasting and natural seasoning. However, it is unclear whether the odor of oak varies according to different geographical regions and pedoclimatic conditions. Especially in view of the actual challenges in forestry in relation to climate change, the present study aimed at elucidating the odorous constituents of nine natural oak samples from Germany, Austria and Hungary with respect to these influencing parameters. The odor profiles of the oaks were compared, the potent odorants were determined, and selected odorants were quantified using stable isotope dilution assays (SIDA). The majority of the identified odorants in all samples were fatty acid degradation products, followed by a series of odorants with terpenoic structure and others resulting from the degradation of lignin. Several different odorants including 2-propenoic acid and cinnamaldehyde are reported here for the first time in oaks from different growth regions. Odor activity values (OAVs), calculated based on odor thresholds (OTs) in water, revealed hexanal, (E)-2-nonenal, (Z)-3-hexenal, eugenol, vanillin, and whiskey lactone as potent odorants for the oak odor. Principal component analysis of the data obtained from sensory evaluation, comparative aroma extract dilution analysis (cAEDA) and their corresponding quantified odorants showed that the highest separation rate was obtained for Hungarian oak, whereas Austrian and Bavarian oak samples were more similar. Recombination experiments by mixing the dominant odorants in their naturally occurring concentrations revealed a good agreement of the smell properties of the model mixture with the smell of the respective original sample. These findings aim at evaluating and establishing a better understanding of the distinctive smell of oak wood and demonstrated the prospects of new oak sources.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Comparative aroma extract dilution analysis (cAEDA); Gas chromatography olfactometry (GC-O); Oak wood; Odor recombination; Odorant; Pedoclimatic conditions; Stable isotope dilution assays (SIDA)

Identification of odorous compounds in oak wood using odor extract dilution analysis and two-dimensional gas chromatography-mass spectrometry/olfactometry - Ghadiriasli, Rahil; Wagenstaller, Maria; Büttner, Andrea (Analytical and Bioanalytical Chemistry, 2018)
Keywords: Odor extract dilution analysis (OEDA); Odorant; Gas chromatography olfactometry (GC-O); Heart-cut two-dimensional gas chromatography-mass spectrometry/olfactometry; Volatile

Molecular and sensory characterization of odorants in Cembran pine (Pinus cembra L.) from different geographic regions - Ghadiriasli, Rahil; Mahmoud, Mohamed A.A.; Wagenstaller, Maria; van de Kuilen, Jan Willem; Büttner, Andrea (Talanta, 2020)
The wood of the Cembran pine (Pinus cembra L.), also known as Swiss pine, Arolla pine or Stone pine, has a prominent and long-lasting odor which has been reported to relieve stress in humans. However, the odorants responsible for this are unknown and it is also unclear whether the odor profile depends on the origin of the trees, namely different geographical regions and pedoclimatic conditions. Therefore, in this study human sensory analyses together with isolation and analysis of the target odorants via solvent-assisted flavor evaporation were performed. Afterwards, comparative odor extract dilution analysis (cOEDA) was applied to investigate the odorous constituents of pinewood samples from forests in Austria and Italy. Specific odorants were thereby identified using one-dimensional and two-dimensional gas chromatography-mass spectrometry/olfactometry using two capillary columns with different polarities (DB-5 and DB-FFAP). In total, 103 odorants were detected with successful identification of 98 of these substances. The identified odorants were predominately monoterpenes and sesquiterpenes as well as organic acids. Several compounds including germacrene D, thymol, carvacrol, rotundone, β-caryophyllene, α-humulene, cinnamaldehyde, and ethyl cinnamate are reported here for the first time as odorous constituents of pinewood. Principal component analysis of the data obtained from sensory evaluation and cOEDA indicated that terpenes and sesquiterpenes were correlated with higher hedonic rates for the wood samples. Moreover, a Mantel test between the geographical distances of the trees and their sensory and cOEDA values demonstrated that the origin of the trees had a significant impact on the sensory characteristics of the wood, in agreement with the differences in the relative proportions of different volatile components. As such, the odor of Cembran pinewood is prone to variation but, yet, unique.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Gas chromatography-olfactometry; Mass spectrometry; Odor extract dilution analysis; Pinewood; Terpene; Volatile organic compound

Smoky, Vanilla, or Clove-Like? Structure-Odor Activity Relationships of Guaiacol Derivatives - Ghadiriasli, Rahil; Lorber, Katja; Wagenstaller, M.; Büttner, Andrea (SEX, SMOKE, AND SPIRITS: THE ROLE OF CHEMISTRY, 2019)
CRIS-Team WoS Importer:2020-03-20

Smoky, Vanilla, or Clove-Like? Structure-Odor Activity Relationships of Guaiacol Derivatives - Ghadiriasli, Rahil; Lorber, Katja; Wagenstaller, M.; Büttner, Andrea (Sex, Smoke, and Spirits: The Role of Chemistry, 2019)
Smoky smells, primarily comprising guaiacols, phenols, and cresols, are enjoyed in diverse foods and beverages, such as whiskey, smoked ham, cheese, or baked goods, such as pizza. They contribute to the flavor and smell experience when smoking tobacco products or when sitting at a fireplace. In other cases, smoky smells indicate potential locations of pyrolytic and combustion processes and may act as alarm signals. In the animal kingdom, interestingly, some compounds related to common constituents of smoke may serve as chemo-communication tools or even pheromones. However, previous studies on the odor properties of alkylated and halogenated guaiacols, phenols, and cresols demonstrate that smoky smell is not the same for everybody. When resolving the underlying chemical structures and carrying out systematic structure-odor activity relationship investigations, one realizes that there are obviously more complicated considerations for each of us in the smell of smoke. This chapter gives an overview of the sensory data of guaiacol and selected structurally related odorants, such as alkylated, alkenylated, methoxylated, and halogenated guaiacol derivatives.
CRIS-Team Scopus Importer:2019-11-01

Unexpected impact of 2-methylisoborneol as off-odour substance in aged wines. - Lopez Pinar, Angela; Ghadiriasli, Rahil; Darriet, Philippe; Büttner, Andrea (Food Chemistry, 2017)

Unexpected impact of 2-methylisoborneol as off-odour substance in aged wines - Lopez Pinar, Angela; Ghadiriasli, Rahil; Darriet, Philippe; Büttner, Andrea (Food Chemistry, 2017)
Four Pinot noir wines from Burgundy were investigated by gas chromatography-olfactometry, with regard to the presence of earthy-smelling compounds. 2-Methylisoborneol (2-MIB) was detected in two of these wines, although the samples were seven years old, contradicting previous reports that this substance is unstable in wine and must. In order to investigate this seemingly paradoxical situation, 2-MIB stability was reinvestigated in wine and in model solution starting with an elevated initial concentration. Although 2-MIB concentration greatly decreased during the 90 days of storage, the final concentration measured in both media was well above the odour threshold of the substance. Based on the observation of a decelerating decrease of 2-MIB with time, it was concluded that this substance can still be detected in wine and can induce, in this case, an earthy off-odour on condition that the start concentration is high enough.
Keywords: Off-odours; Gas chromatography-olfactometry (GC-O); 2-Methyl-2-bornene; 2-Methylenebornane; Musty; Mouldy; Smell; Aroma